Comparative anatomy of reproductive structures in Cyclanthaceae (Pandanales) - Sajo, Maria das Graças [UNESP]; Lombardi, Julio Antonio [UNESP]; Forzza, Rafaela C.; Rudall, Paula J. (Univ Chicago Press, 2014)
Premise of research. The Neotropical family Cyclanthaceae is one of five families of the order Pandanales, which includes some misfit taxa that are morphologically highly anomalous. In the taxonomically isolated genus Cyclanthus, which is sister to all other Cyclanthaceae, individual flowers are not readily distinguishable. Instead, flowers are replaced by discoidal rings that encircle the inflorescence. We compare features that are shared among misfit taxa.Methodology. We use scanning electron microscopy and light microscopy to describe the reproductive structures of both subfamilies of Cyclanthaceae, including Cyclanthus bipartitus (Cyclanthoideae) and several Carludovicoideae.Pivotal results. Our pollination observations on Carludovica palmata flowers contrast with some other reports, because we observed only small black bees of the Meliponini tribe visiting this species. The anomalous reproductive structures of Cyclanthus show some features in common with Carludovicoideae, especially the presence of large axial mucilage canals. However, Cyclanthus differs from Carludovicoideae in several respects; for example, the outer integument is relatively poorly developed in Cyclanthus. The staminodes on male flowers of Carludovicoideae are secretory, with elongated epidermal cells.Conclusions. We interpret as staminodes the sterile secretory lobes that are present on the androphore of most Carludovicoideae. Our observations enhance existing knowledge of floral anatomy of Cyclanthaceae, especially Cyclanthus, and provide a comparative basis for future studies of Pandanales.
Keywords: anatomy; Carludovicoideae; Cyclanthus; pseudanthia; staminodes; tapetum